Retrieval of Urban Land Surface Temperature Matrices from Remotely Sensed Data: An Overview - Felix , Ike; Chiedozie , Mbah, Isaac; Ejimofor , Ochi (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
In the evaluation and monitoring of environmental and ecological processes, remote sensing is becoming a force to be reckoned with. The role of temperature as a tool for monitoring urban expansion and heat islands in cities around the world was examined in this study. The research went on discussing the role of various land-use/land-cover changes as verifiable inputs in determining the urban heat Island threshold. The study equally found that in the case study locations, Landsat thermal data is frequently used to compute land surface temperature. The imagery' NDVI values are used to see if they correlate with LST. We also discovered that supervised classification is the optimal strategy for determining land use classes when the goal of a study is to obtain temperature profiles in any metropolitan region. In contrast to other methods like mono-window and split-window, brightness temperature is determined to be popular in the literature analyzed.